Assessment of wasted myocardial work: a novel method to quantify energy loss due to uncoordinated left ventricular contractions - Russell, Kristoffer; Eriksen, Morten; Aaberge, Lars; Wilhelmsen, Nils; Skulstad, Helge; Gjesdal, Ola; Edvardsen, Thor; Smiseth, Otto A. (American journal of physiology. Heart and circulatory physiology, 2013)
Left ventricular (LV) dyssynchrony reduces myocardial efficiency because work performed by one segment is wasted by stretching other segments. In the present study, we introduce a novel noninvasive clinical method that quantifies wasted energy as the ratio between work consumed during segmental lengthening (wasted work) divided by work during segmental shortening. The wasted work ratio (WWR) principle was studied in 6 anesthetized dogs with left bundle branch block (LBBB) and in 28 patients with cardiomyopathy, including 12 patients with LBBB and 10 patients with cardiac resynchronization therapy. Twenty healthy individuals served as controls. Myocardial strain was measured by speckle tracking echocardiography, and LV pressure (LVP) was measured by micromanometer and a previously validated noninvasive method. Segmental work was calculated by multiplying strain rate and LVP to get instantaneous power, which was integrated to give work as a function of time. A global WWR was also calculated. In dogs, WWR by estimated LVP and strain showed a strong correlation ( r = 0.94) and good agreement with WWR by the LV micromanometer and myocardial segment length by sonomicrometry. In patients, noninvasive WWR showed a strong correlation ( r = 0.96) and good agreement with WWR using the LV micromanometer. Global WWR was 0.09 ± 0.03 in healthy control subjects, 0.36 ± 0.16 in patients with LBBB, and 0.21 ± 0.09 in cardiomyopathy patients without LBBB. Cardiac resynchronization therapy reduced global WWR from 0.36 ± 0.16 to 0.17 ± 0.07 ( P < 0.001). In conclusion, energy loss due to incoordinated contractions can be quantified noninvasively as the LV WWR. This method may be applied to evaluate the mechanical impact of dyssynchrony.